Economic evaluation in clinical trials - Glick, Henry; Doshi, Jalpa A.; Sonnad, Seema S.; Polsky, Daniel (Oxford : Oxford University Press, 2015)
A a practical guide to the techniques and issues involved in conducting economic evaluation in ongoing clinical trials, supported with detailed advice on the design and analysis of studies including analysis of cost effectiveness and methodological integrity.
1. Introduction to economic evaluations in clinical trials ; 2. Designing economic evaluations in clinical trials ; 3. Valuing medical service use ; 4. Assessing quality-adjusted life years ; 5. Analyzing cost ; 6. Analyzing censored cost ; 7. Comparing cost and effect: point estimates for cost-effectiveness ratios and net monetary benefit ; 8. Understanding sampling uncertainty: the concepts ; 9. Sampling uncertainty: calculation, sample size and power, and decision criteria ; 10. Transferability of the results from trials ; 11. Relevance of trial-based economic analyses
Includes index.
Previous edition: 2007.
Keywords: Clinical trials -- Economic aspects; Outcome assessment (Medical care) -- Economic aspects